2018
DOI: 10.1038/s41598-018-35246-1
|View full text |Cite
|
Sign up to set email alerts
|

Controlling aflatoxin contamination and propagation of Aspergillus flavus by a soy-fermenting Aspergillus oryzae strain

Abstract: Aflatoxins (AFs) are a group of carcinogenic and immunosuppressive mycotoxins that threaten global food safety. Globally, over 4.5 billion people are exposed to unmonitored levels of AFs. Aspergillus flavus is the major source of AF contamination in agricultural crops. One approach to reduce levels of AFs in agricultural commodities is to apply a non-aflatoxigenic competitor, e.g., Afla-Guard, to crop fields. In this study, we demonstrate that the food fermenting Aspergillus oryzae M2040 strain, isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 61 publications
6
61
0
Order By: Relevance
“…Representative chromatograms of A. oryzae NRRL 3483 grown in slant cultivation medium are shown in Figure 4E,F. In addition, A. oryzae M2040 and A. oryzae NRRL RIB40 were unable to produce any types of AFs when grown in different culture medium, as shown in previous studies [28,29]. In summary, in this work, we report a HPLC method coupled with DAD and FLD detectors that would be the first and only validated tool for simultaneous quantitation of AFB1, AFB2, AFG1, and AFG2 in three different laboratory culture conditions.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Representative chromatograms of A. oryzae NRRL 3483 grown in slant cultivation medium are shown in Figure 4E,F. In addition, A. oryzae M2040 and A. oryzae NRRL RIB40 were unable to produce any types of AFs when grown in different culture medium, as shown in previous studies [28,29]. In summary, in this work, we report a HPLC method coupled with DAD and FLD detectors that would be the first and only validated tool for simultaneous quantitation of AFB1, AFB2, AFG1, and AFG2 in three different laboratory culture conditions.…”
Section: Resultssupporting
confidence: 80%
“…Representative chromatograms of A. oryzae NRRL 3483 grown in slant cultivation medium are shown in Figure 4E,F. In addition, A. oryzae M2040 and A. oryzae NRRL RIB40 were unable to produce any types of AFs when grown in different culture medium, as shown in previous studies [28,29]. Figure 4C,D), respectively.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…These toxins can cause several disorders at the consumer manifested by many syndromes such as hepatotoxic, neurotoxic, mutagenic, teratogenic, carcinogenic and immunosuppressive effects (Alshannaq et al, 2018;Ezekiel et al, 2018). These effects can be manifested by gastroenteritis, haemorrhage, convulsions, paralysis, oestrogen, kidney and liver damage leading to cancer (Okpala and Ifeoma, 2019;Gauthier, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A. oryzae, the nontoxigenic domesticated ecotype of A. flavus, is used as a "Generally Recognized As Safe (GRAS)" microorganism for food fermentation [76,77]. Alshannaq et al demonstrated that co-inoculation with A. oryzae and A. flavus on peanuts with a ratio of 1:100 could effectively inhibit AFB 1 production [41]. The species of A. clavatus could secrete ribonuclease [78], while Skouri-Gargouri and Gargouri revealed that A. clavatus could inhibit the growth of several plant pathogens such as Fusariuym oxysporum and Aspergillus niger due to the secretion of an antifungal peptide [42].…”
Section: Nontoxigenic Aspergillus Sppmentioning
confidence: 99%